A Noteon Saving-Investment Correlations in the EMS. (IMF Working Papers; Working Paper, 1990)
This paper extends recent work by Feldstein and Horioka (1980) and Bayoumi (1990), and examines saving-investment correlations for industrial countries in the post-war period. The focus of the enquiry is on differences observed between EMS and non-EMS countries. It is seen that the EMS countries exhibit much lower saving-investment correlations than their non-EMS counterparts. This result supports the hypothesis that exchange rate stability achieved in the EMS has been an important factor in promoting international capital mobility.